Black middle class delinquents - Hassett-Walker, Connie R. (Criminal justice recent scholarship, 2009)
Introduction -- Theoretical framework -- The Black middle class and crime -- Empirical research on class and crime -- Data and methodology -- Cross-sectional bivariate results -- Cross-sectional multivariate results for Blacks -- Cross-sectional comparative multivariate results -- Longitudinal data and analyses -- In conclusion: A call to fellow criminologists